2012
DOI: 10.1111/j.1365-2966.2012.21402.x
|View full text |Cite
|
Sign up to set email alerts
|

The WiggleZ Dark Energy Survey: the transition to large-scale cosmic homogeneity

Abstract: We have made the largest volume measurement to date of the transition to large‐scale homogeneity in the distribution of galaxies. We use the WiggleZ survey, a spectroscopic survey of over 200 000 blue galaxies in a cosmic volume of ∼1 h−3 Gpc3. A new method of defining the ‘homogeneity scale' is presented, which is more robust than methods previously used in the literature, and which can be easily compared between different surveys. Due to the large cosmic depth of WiggleZ (up to z = 1), we are able to make th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
204
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(223 citation statements)
references
References 95 publications
9
204
3
4
Order By: Relevance
“…The recent data, reported in the Monthly Notices of the Royal Astronomical Society ("The WiggleZ Dark Energy Survey: the transition to large-scale cosmic homogeneity"), disprove the hierarchical model in which it is argued, by some theorists, that the entire universe never becomes homogenous and that matter is clustered on ever larger scales, much like one of Mandelbrot's famous fractals. The finding is considered to be extremely significant for cosmology [16].…”
Section: Preliminariesmentioning
confidence: 98%
See 1 more Smart Citation
“…The recent data, reported in the Monthly Notices of the Royal Astronomical Society ("The WiggleZ Dark Energy Survey: the transition to large-scale cosmic homogeneity"), disprove the hierarchical model in which it is argued, by some theorists, that the entire universe never becomes homogenous and that matter is clustered on ever larger scales, much like one of Mandelbrot's famous fractals. The finding is considered to be extremely significant for cosmology [16].…”
Section: Preliminariesmentioning
confidence: 98%
“…Thus, the total intrinsic redshift that the photon acquires during a complete transit of the cosmic gravity well is z GC = 2×0.0067 = 0.0134 (16) What happens during the photon's propagation in the interior of the cluster? Photons that penetrate the cloud-cluster, of our thought experiment earlier, without being intercepted or diverted would, according to the velocity-differential principle, become blueshifted.…”
Section: Inbound Photonmentioning
confidence: 99%
“…O Princípio Cosmológico permaneceu apenas uma hipótese inteligente até que dados empíricos sólidos confirmando a homogeneidade e isotropia em grande escala fossem finalmente obtidos no final do século XX [11]. Pesquisas sugerem que o Universo passa a ser realmente homogêneo e isotrópico em escalas superiores a 100Mpc [6,12]; em escalas menores existem grandes inomogeneidades, como galáxias, aglomerados e superaglomerados de galáxias.…”
Section: Geometria Dinâmica E Os Componentes Do Fluido Cosmológicounclassified
“…In 2012, Scrimgeour et al conclusively demonstrated that the large scale structure of the universe beyond the scale of approximately 70 MPC / hours, was close to the value found by . ueir s [7].…”
Section: International Letters Of Chemistry Physics and Astronomy Vomentioning
confidence: 99%